Hormones, autonomic nervous system activity, and criminal behavior - Armstrong, Todd A. (Journal of crime and justice, 2025)
Evidence that hormones and autonomic nervous system activity exert a joint influence on antisocial behavior suggests that they may work together to explain risk for criminal behavior. Thus, the current study explored the interactive effects of hormones (testosterone, cortisol) and ANS activity (heart rate, skin conductance) on impulsive and violent criminal behavior in a large sample of university students (n = 495). Initial analyses found positive direct associations between impulsive and violent crime and both testosterone and cortisol and a negative direct association between heart rate reactivity and impulsive and violent crime. Subsequent analyses revealed a statistically significant interaction between testosterone and heart rate in association with impulsive and violent criminal behavior. The positive association between testosterone and crime became statistically significant at −.29 standard deviations below the mean (HR = 76.44) and grew stronger as heart rate decreased from this point. The interaction between testosterone and heart rate remains statistically significant after the inclusion of controls for constructs that feature prominently in contemporary criminological theories. Other interactions between hormones and ANS activity were present but were not consistent across alternative model specifications.